2022
DOI: 10.3389/fped.2022.817471
|View full text |Cite
|
Sign up to set email alerts
|

Parental and School Influences on Character Attributes Among Chinese Adolescents

Abstract: ObjectivesWhile there are many theoretical propositions on parental and school impacts on character formation among adolescents, limited empirical evidence is available. To fill the research gaps, this study examined how parental factors (e.g., behavioral control, support, parent–child relationship, and psychological control) and school factors (teacher–student relationship and student–student relationship) affect adolescents' character attributes in the areas of “treating others well,” “self-discipline and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…A person's attitude and behavior are developed in various social contexts, where values are one of the first steps of moral development in the family; parents not only transmit norms, standards and values, but also strengthen them through daily parenting practices [34]. The internalization of parents' values depends on the age of the children and the relationship between parents and children, which promotes the assimilation of values based on the closeness and support of family members [35].…”
Section: Literature Review: Value Attitudes and The Significance Of T...mentioning
confidence: 99%
“…A person's attitude and behavior are developed in various social contexts, where values are one of the first steps of moral development in the family; parents not only transmit norms, standards and values, but also strengthen them through daily parenting practices [34]. The internalization of parents' values depends on the age of the children and the relationship between parents and children, which promotes the assimilation of values based on the closeness and support of family members [35].…”
Section: Literature Review: Value Attitudes and The Significance Of T...mentioning
confidence: 99%
“…To some extent, these findings echo the previous proposition that psychological control is a dysfunctional parenting practice impairing the child's healthy functioning in different societies ( 19 , 59 ). Nevertheless, some prior studies reported that parental psychological control insignificantly affects a child's developmental outcomes ( 54 , 55 , 57 ). The weak or insignificant effect of parental psychological control may imply different interpretations of parenting practices in Chinese societies.…”
Section: Discussionmentioning
confidence: 98%
“…Parental behavioral control and psychological control were measured by the respective subscales derived from the validated Chinese Parent-Child Subsystem Quality Scale that has been frequently used to measure Chinese adolescents' perceptions of parental factors ( 53 , 54 ). Each parent's behavioral control was assessed using seven items (e.g., “My father/mother asked me about what I did after school” and “My father/mother actively understands my afterschool activities”), and psychological control was measured using four items (e.g., “My father/mother often wants to change my mind or feelings for things” and “My father/mother values his/her thoughts and overlooks mine”).…”
Section: Methodsmentioning
confidence: 99%
“…Self-discipline and perseverance are traits that determine long-term adherence to tasks to achieve long-term goals. This trait is not associated with personality traits, family culture and contradictions, and social environments [20]. It is suggested that Chinese parents should not only improve the condition of life and work for the patients, but also give more emotional care to AIS patients, to help them develop the habit of self-discipline.…”
Section: Discussionmentioning
confidence: 99%